(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: The science of information security has become a concern of many researchers, whose efforts are trying to come up with solutions and technologies that ensure the transfer of information in a more secure manner through the network, especially the Internet, without any penetration of that information. Due to the importance of digital data sent between the two parties through an insecure channel. As a result, there are many technologies and methods that are currently used in information security, including steganography and encryption. This paper proposes a safe method for text and audio files by encrypting them using the RC4 algorithm that relies on the chaos system. This system generates chaotic values ​​that increase the randomness of the key and thus difficult to break. Then use the embedding technique in the color or grayscale images using the LSB sequential algorithm. I relied on hiding in the edges of the image, which were areas of strength where the change was not noticeable. The results showed a high ability to include data, as the PSNR scale reached more than 50, and the retrieved data was obtained without errors.